(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article examines the problems of preventing economic crimes, in particular, crimes committed without the use of force, i.e., robbery, embezzlement or embezzlement, fraud, theft, and the administration of justice on them.